The Problem of Rabies Vaccination in Children; an Analysis of Children Bitten by Rabid and Rabid-Suspected-Animals - Muzief Munir (Indonesian Pediatric Society, 1980)
The analysis of 234 Children, under 14 years of age, with the diagnosis of an animal bite was carried out in an attempt to find out problems of rabies vaccination in the children. One of the most important factors in eliminating or at least greatly reducing rabies, is the public dissemination of information concerning not only the danger of unbzjected animals, but how rabies can be prevented or terminated if treated immediately. Two ml of NTV was given for 14 consecutive days regardless of Ã‚Â·the age of the victims, the site and the severity of the wounds, and the time span between the bite and the start of vaccinaton. ARS was never used regardless of the site and the severity of the wounds. It is clearly seen from this analysis that the regime used in this report is safe and effective enough to prevent the victims from contracting rabies as long as the vaccination can be started within 10 days after being bitten. ARS must be given to the victims with head or back bites when the lapse of time between the bite and the start of vaccination is more than 10 days and can justifiably be instituted in arm and leg bite victims when the time span between the bite and the start of vaccinaion is more than 21 days.